HUBUNGAN SELF REGULATED LEARNING DENGAN PRESTASI AKADEMIK MAHASISWA KEPERAWATAN FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA DI MASA PANDEMI COVID-19 - Ina, Yohana Ventalia; Sawitri, Ni Komang Ari; Raya, Nyoman Agus Jagat (Coping: Community of Publishing in Nursing; Vol 12 No 3 (2024): Juni 2024DO - 10.24843/coping.2024.v12.i03.p06, 2024)
Self regulated learning is the process of a learner organizing himself, behavior, feelings, and motivation to achieve the desired purpose of learning. Academic achievement is a change in abilities that can grow over time because of the learning process. The purpose of this study is to identify the relationship of self regulated learning with the academic achievement of nursing students at the time of the covid-19 pandemic. The study uses a descriptive correlation method with a sectional cross design. The removal of samples in this study uses the proportionate stratified random sampling over 1 week and 2 days with the number of samples 137. Data collection uses a questionnaire developed by Wolters and modified by Riani and Rastafary. Data analysis research uses the spearman rank statistical test. Research shows self regulation learning and academic achievement of three generations on nursing students have significant relationships, class of 2018 (p=0,000), class 2019 (p= 0,003) and force 2020 (p= 0,001), the relationship of this study is positive (r=0,534; r= 0,440; r=0,454). Applications in the world of nursing that can be done by student instruction to implement self regulation learning to improve and improve motivation to achieve learning goals. Self regulated learning can affect academic achievement, so this study helps students to identify the level of self regulated learning that is currently under their control.